Storiografia e identità dei centri minori italiani tra la fine del medioevo e l'Ottocento - Varanini, Gian Maria (Centro di Studi sulla Civiltà del Tardo Medioevo San Miniato, 2013)
Between the sixteenth and nineteenth centuries, the elites (secular and ecclesiastical) of the many villages, castles, smaller urban centres that make the Italian landscape so unique, started to deeply rethink the past of their "small homeland". Roman (but also pre-Roman) heritage and medieval tradition are at the centre of interest; bold "inventions" and manipulations alternate with searches for a solid erudite structure. The essays published here concern the Italian regions of Piedmont, Romagna, Emilia, Tuscany, Marche, Umbria, Terra di Bari, Campania. In the essays, a strong sense of identity and a robust self-awareness emerges; ultimately, this is the vitality of a connective tissue of settlements featuring an "original character" relevant in the Italian historical events from the Middle Ages to the present day.